2001
DOI: 10.1063/1.1333738
|View full text |Cite
|
Sign up to set email alerts
|

Structure of nanocrystalline Re–Si thin film composites and their unusual thermoelectric properties

Abstract: The structure of nanocrystalline rhenium-silicon composite ReSi x films with 1.4ϽxϽ2.2 has been studied as a function of the time by means of high temperature x-ray diffraction and transmission electron microscopy. Simultaneously, the thermoelectric transport properties were measured during the heat treatment. The nanocrystallization was achieved by annealing of amorphous films deposited onto oxidized Si wafers by magnetron cosputtering. The crystallization process is characterized by a decreasing average crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Since the crystallization is characterized by an incubation time, t inc (see Fig. 3), which is strongly dependent on annealing temperature [14], the peculiarity in the ρ(T ) and S(T ) dependences are observed at a higher temperature in comparison with XRD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the crystallization is characterized by an incubation time, t inc (see Fig. 3), which is strongly dependent on annealing temperature [14], the peculiarity in the ρ(T ) and S(T ) dependences are observed at a higher temperature in comparison with XRD.…”
Section: Resultsmentioning
confidence: 99%
“…The state of the film composite in the course of its transformation from amorphous to NC composite was controlled by means of the in-situ transport measurements -simultaneous measurements of electrical resistivity (ρ = 1/σ) and S. Standard DC 4 points configuration was used in the resistivity measurements, while differential method was utilized for thermopower [13]. Transmission Electron Microscopy and X-Ray Diffraction were utilized for structural characterization of the samples [14].…”
Section: Methodsmentioning
confidence: 99%
“…The mean grain size versus annealing time shows an unexpected behaviour. Because of a preferred growth of large grains up to 100 nm at the beginning of the crystallisation and the formation of smaller grains on later annealing stages [8], the grain size decreases with increasing annealing time. The time up to which the larger grains are growing is limited to about 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, results of X-ray investigations after long annealing times [8] have been used for calibrating the ordinate. On the other hand, measurements of the thermopower S have been carried out as function of the annealing time t in He atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1993, when Hicks and Dresselhaus [1] reported that the dimensionless thermoelectric figure of merit ZT (= 2 T/ , here , , and are the electrical conductivity, the Seebeck coefficient, and the thermal conductivity of the material, respectively, and T is absolute temperature) of a material can be markedly increased as its dimensionality is reduced, the preparation and thermoelectric properties of nanostructured materials have attracted more and more attention [2][3][4][5][6][7][8][9]. For example, Lin et al [2,3] studied the transport properties of Bi and Bi 1-x Sb x nanowires and found that the Seebeck coefficient of Bi nanowires and the electrical conductivity of Bi 1-x Sb x nanowires both dramatically increased as the diameter of the corresponding nanowires decreased.…”
Section: Introductionmentioning
confidence: 99%